2017
DOI: 10.1073/pnas.1700010114
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nucleobases in a Miller–Urey reducing atmosphere

Abstract: The Miller-Urey experiments pioneered modern research on the molecular origins of life, but their actual relevance in this field was later questioned because the gas mixture used in their research is considered too reducing with respect to the most accepted hypotheses for the conditions on primordial Earth. In particular, the production of only amino acids has been taken as evidence of the limited relevance of the results. Here, we report an experimental work, combined with state-of-the-art computational metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
138
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(138 citation statements)
references
References 72 publications
0
138
0
Order By: Relevance
“…Formamide-based chemistry is a broadly discussed scenario relating to the origin of biomolecules (Saladino et al 2004(Saladino et al , 2012bFerus et al 2011bFerus et al , 2012Ferus et al , 2014Ferus et al , 2017bSaitta & Saija 2014;Pino et al 2015;Šponer et al 2016a,b;Adam et al 2018;Becker et al 2018;Benner et al 2012). Besides the traditional HCNand reducing-atmospheres based biomolecules synthesis (Ferris et al 1974;Yuasa et al 1984;Levy et al 1999;Sutherland 2016;Civiš et al 2017), the current evidence shows that the formamide molecule did not necessary play role of merely starting parent prebiotic precursor, but also it could serve as an intermediate compound in prebiotic synthesis (Ferus et al 2017b).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Formamide-based chemistry is a broadly discussed scenario relating to the origin of biomolecules (Saladino et al 2004(Saladino et al , 2012bFerus et al 2011bFerus et al , 2012Ferus et al , 2014Ferus et al , 2017bSaitta & Saija 2014;Pino et al 2015;Šponer et al 2016a,b;Adam et al 2018;Becker et al 2018;Benner et al 2012). Besides the traditional HCNand reducing-atmospheres based biomolecules synthesis (Ferris et al 1974;Yuasa et al 1984;Levy et al 1999;Sutherland 2016;Civiš et al 2017), the current evidence shows that the formamide molecule did not necessary play role of merely starting parent prebiotic precursor, but also it could serve as an intermediate compound in prebiotic synthesis (Ferus et al 2017b).…”
Section: Introductionmentioning
confidence: 74%
“…Besides the traditional HCNand reducing-atmospheres based biomolecules synthesis (Ferris et al 1974;Yuasa et al 1984;Levy et al 1999;Sutherland 2016;Civiš et al 2017), the current evidence shows that the formamide molecule did not necessary play role of merely starting parent prebiotic precursor, but also it could serve as an intermediate compound in prebiotic synthesis (Ferus et al 2017b). In fact, it has been demonstrated that it acted either as substrate or as intermediate in a series of complex reactions starting from very reactive small radicals and leading to a broad palette of biomolecules, for example, all the canonical nucleobases of the genetic code, ribose and other sugars, amino acids or even fatty acids (Saladino et al 2011(Saladino et al , 2015Ferus et al 2015b).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Though guanine is less abundantly made, it can occur in the same order of concentration as adenine (Borquez et al 2005). Other possible nucleobase sources such as impact on a reducing atmosphere also supply the synthetic impetus for both standard purines (Ferus et al 2017). Most relevantly, adenine and guanine of extraterrestrial origin occur together in multiple carbonaceous chondrite meteorites (Callahan et al 2011).…”
Section: All Nucleobases For Para-templating From One Primordial Syntmentioning
confidence: 99%